A Rare Scenario of Acute Traumatic Thoracic Disc Herniation and Review of the Literature - Abolfazl Rahimizadeh; Zahed Malekmohammadi; Walter Williamson; Mahan Mahan (Iranian Journal of Neurosurgery, 2022)
Background and Importance: Sequestrated thoracic disc herniation after a traumatic event without an apparent spinal fracture or dislocation is an extremely rare scenario. Case Presentation: Evaluation of an elderly female with acute paraparesis secondary to a fall down to the ground revealed a right-sided extruded disc at the level of T10-T11. At 6-month follow-up, she made a dramatic recovery following an appropriate surgical intervention. Conclusion: With occurrence of acute paraparesis following a traumatic event, MRI of the vertebral column is necessary, even in the absence of tomographic evidence of fracture-dislocation